Handout Design of Scientific-Based Mathematics and Inquiry Strategies - Wahyuni, Sutri (Journal Evaluation in Education (JEE), 2023)
Purpose of the study: This study aimed to produce scientifically based mathematics handout products and inquiry strategies on opportunity material in class seven which is valid according to experts, and to determine the effectiveness of the learning process.Methodology: This type of research is design and development research using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The instruments used in this study were: (1) validation sheets for material experts; (2) validation sheets for handout design experts, both of which are used to assess the feasibility of teaching materials; (3) teacher response sheet; (4) student response sheets, these sheets are used to assess the validity of teaching materials; (5) student observation sheets about student activity, used to see student activity; and (6) post-test question sheets, used to see the effectiveness of the learning process.Main Findings: From the analysis carried out on the final test of opportunity material, the average post-test score was 93.3 with a percentage of student completeness of 82.5%, and the results of observations of student activity in learning were 73.32% in the "good" category. The study results show that the learning process using scientific-based mathematics handouts and inquiry strategies runs effectively.Novelty/Originality of this study: The latest update in this research is to develop a scientifically based mathematics handout and an inquiry strategy on probability material. There has been no research on developing scientifically based mathematics handouts and inquiry strategies on opportunities. Therefore, this study complements previous research.